Improvement the bearing capacity of the soil which is supporting the shallow foundation by using bored short micro-piles (Baghdad Science Journal, 2025)
In this paper , concrete micro-piles were used to improve the bearing capacity of the soil which is supporting the shallow foundation by using groups of (4; 6 and 9)bored short micro-piles which have, (D=0.125m and D=0.1m), and length to diameter ratio (L/D) equal to (6; 10 and 12) respectively.To calculate the bearing capacity of the micro-piles,(Tomlinson) and (Lamda) methods were used; also the soil properties were taken from Al-Muthana airport,(Al-Qyssi,2001) [1]. The results show that; increasing the number of piles and/ or the diameters and lengths; and the interaction between the bearing capacity of the shallow foundation with the bearing capacity of the pile group which leads to increasing the strength against the external loads; and the maximum bearing capacity was, when 9 piles with (L/D=12) was used. The improving ratio in the bearing capacity was (90%) compared with the bearing capacity of a (1×1) m shallow foundation without any piles.The results show that, the Tomlinson method of analysis produce lower results than the Lamda method by a ratio of (2-6) %. The results show also that the use of bored short micro-piles with (D=0.125m); (L/D=12) and number of 4-piles better than the (9) bored short micro-piles which have (D=0.1m).